Metode Penyelesaian Dalam Kajian Matan Hadis-Hadis Kontroversial - soi, drs rahmat (Fakultas Adab dan Humaniora UIN Alauddin, 2014)
This writing discusses controversial hadits and the way of understanding the hadis, using various methods and interpretation technique. Although a hadis is recognized controversial, it doesnât mean that it cannot be solved. Some ulamas of hadis have discussed and put forward some alternative arguments to come to final conclusion. Some methods such as; al-Jamu, al-Tarjih, al-Nasikh, wa al-Mansukh dan al-Tauqif, as well asÂ textual, contextual interpretation, linguistic or historical approachÂ can be regardedÂ as ways to understand the essentian meaning of the controversial hadis.